Effect of polyherbal mixture supplementation on incidence of mastitis and milk production in postpartum Murrah buffaloes - Japheth, Konii Puhle; Kumaresan, Arumugam; Ganaie, Bilal Ahmad; Oberoi, Parvinder Singh; Lathwal, Surrender Singh; Singh, Pawan (Indian Journal of Dairy Science, 2019)
The study was conducted at ICAR-NDRI to investigate the effect of polyherbal mixture supplementation on incidence of mastitis and milk production in postpartum Murrah buffaloes. A total of 60 buffaloes were utilized for the study and were randomly classified into two groups viz. control and treatment group (each 30 buffaloes). Buffaloes in the control group were fed with the routine ration as per the feeding schedule of NDRI (NRC, 2001+ 10% extra energy). Buffaloes in the treatment group were supplemented with polyherbal mixture containing 25g each of Ajwain, Haldi, Jeera, Methi, Saunf, Sowa and Sundh along with 25g of kala namak and 250g jaggery from the day of calving till day 10 of postpartum. The polyherbal mixture was grounded into fine powder, mixed in the concentrate and fed once a day. Milk samples were collected on day 7, 14, 21 and 28 postpartum and examined for somatic cells load by California Mastitis Test (CMT). The lactation total milk yield of both supplemented and non supplemented groups are also recorded. Proportion of Murrah buffaloes that were suspicious for mastitis were 20% (day 7), 10% (day 14), 3.3% (day 21) and 0% (day 28) in supplemented group while it was 36.6% (day 7), 26.6% (day 14), 10% (day 21) and 6.6% (day 28) in control group; there was significant difference (P<0.05) between control and supplemented group on day 7, 21 and 28. The average total milk yield in supplemented group was 2642.87Â±75.45 kg, while it was 2292.27Â±77.65 kg in non supplemented group. The total milk yield was significantly (P<0.05) higher in the supplemented group as compared to control group. It is inferred that supplementation of polyherbal mixture in postpartum Murrah buffaloes minimized the incidence of buffaloes suspicious for mastitis and increased the milk production.